Minimally invasive versus open esophagectomy after neoadjuvant therapy for esophageal cancer: a meta-analysis - Zixian Jin; Kanghao Zhu; Jiajing Sun; Jian Zhang; Bo Zhang (Journal of Cardiothoracic Surgery, 2023)
Abstract Objectives Neoadjuvant therapy and minimally invasive esophagectomy (MIE) are widely used in the comprehensive treatment of esophageal cancer. This study aimed to investigate the advantages of MIE for esophageal cancer after neoadjuvant therapy. Methods Published clinical studies were reviewed and survival data and safety data were extracted. We compared the long-term survival and safety of MIE versus open esophagectomy after neoadjuvant surgery in a series of meta-analyses. Results 6 retrospective studies were included. Overall, MIE could significantly improve the overall survival of patients with esophageal cancer after neoadjuvant therapy compared with open esophagectomy [hazard ratio (HR) = 0.86, 95% confidence interval (CI) (0.75, 0.98)]. Compared with open esophagectomy, MIE could significantly reduce intraoperative blood loss and operative time [mean difference (MD) = −40.28.78, 95% CI (− 62.98, − 17.58); MD = −28.78, 95% CI (− 42.48, − 15.07), respectively]. There was no significant difference in 30-day and 90-day mortality between MIE and open esophagectomy [odds ratio (OR) = 0.42, 95% CI (0.09, 2.01); OR 0.80, 95% CI (0.25, 2.60), respectively]. MIE could not significantly reduce the incidence of anastomotic leakage, recurrent laryngeal nerve palsy and chylothorax [OR 0.70, 95% CI (0.37, 1.32); OR 1.43, 95% CI (0.33, 6.25); HR = 1.79, 95% CI (0.67, 4.75), respectively], but the incidence of pneumonia was significantly reduced [HR = 0.43, 95% CI (0.22, 0.82)]. In addition, the length of hospital stay and the incidence of total complications were significantly reduced after MIE [MD = −2.61, 95% CI (− 3.10, − 2.12); HR = 0.66, 95% CI (0.45, 0.98), respectively]. Conclusion MIE after neoadjuvant therapy is effective and safe. Compared with open esophagectomy, MIE can improve the long-term survival and reduce the incidence of postoperative complications of esophageal cancer patients.